Extracellular Vesicles From the Helminth Fasciola hepatica Prevent DSS-Induced Acute Ulcerative Colitis in a T-Lymphocyte Independent Mode - Roig, Javier; Saiz, Maria L.; Galiano, Alicia; Trelis, Maria; Cantalapiedra, Fernando; Monteagudo, Carlos; Giner, Elisa; Giner, Rosa M.; Recio, M. C.; Bernal, Dolores; Sánchez-Madrid, Francisco; Marcilla, Antonio (Frontiers in Microbiology, 2018)
The complexity of the pathogenesis of inflammatory bowel disease (ulcerative colitis and Crohn’s disease) has led to the quest of empirically drug therapies, combining immunosuppressant agents, biological therapy and modulators of the microbiota. Helminth parasites have been proposed as an alternative treatment of these diseases based on the hygiene hypothesis, but ethical and medical problems arise. Recent reports have proved the utility of parasite materials, mainly excretory/secretory products as therapeutic agents. The identification of extracellular vesicles on those secreted products opens a new field of investigation, since they exert potent immunomodulating effects. To assess the effect of extracellular vesicles produced by helminth parasites to treat ulcerative colitis, we have analyzed whether extracellular vesicles produced by the parasitic helminth Fasciola hepatica can prevent colitis induced by chemical agents in a mouse model. Adult parasites were cultured in vitro and secreted extracellular vesicles were purified and used for immunizing both wild type C57BL/6 and RAG1-/- mice. Control and immunized mice groups were treated with dextran sulfate sodium 7 days after last immunization to promote experimental colitis. The severity of colitis was assessed by disease activity index and histopathological scores. Mucosal cytokine expression was evaluated by ELISA. The activation of NF-kB, COX-2, and MAPK were evaluated by immunoblotting. Administration of extracellular vesicles from F. hepatica ameliorates the pathological symptoms reducing the amount of pro-inflammatory cytokines and interfering with both MAPK and NF-kB pathways. Interestingly, the observed effects do not seem to be mediated by T-cells. Our results indicate that extracellular vesicles from parasitic helminths can modulate immune responses in dextran sulfate sodium (DSS)-induced colitis, exerting a protective effect that should be mediated by other cells distinct from B- and T-lymphocytes.